2013
DOI: 10.11648/j.edu.20130201.11
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Term Projects in Helping Students to Connect Theory with Practice: an Evaluation of Students′ Perspectives.

Abstract: The purpose of this study is to evaluate the effectiveness of term project in helping students to connect theory with practice. A term project is a hands-on assignment that require students to apply ideas, theories, concepts, or principles learned or studied in class to a new situation/real life scenario. Term projects in ENVS 4413 Principles of eco-industrial development are designed to help students connect theory with practice. The aim is to enhance students' learning of the course materials and to give the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(9 reference statements)
0
3
1
Order By: Relevance
“…The present study revealed that the majority of undergraduate nursing students (90.52%) have high level of SDLR(score ≥150).This agree with ,Safavi et al(2010) who stated that majority of Jordanian and Iranian nursing students had high level of SDLR and perceived themselves as independent learner (14).In addition, the majority of students through SDL was a teaching method used alongside other methods, rather than a representation of beliefs about the adult self-learning (15). However, these results contradicted with the study of Lestari and Widjaja kusumah (2009) in Indonesia who indicates that 50% of the students had low to moderates scores for SDLR (16,17,18).These scores are slightly higher than those reported from previous studies in other countries. The mean reason may be: this study indicated that understanding the different components of SDL which are carried out by undergraduate nursing students are very important as study finding students can be adjust their SDL to direct the needs of the students, due to the undergraduate nursing students' state to look at Self-control in self-directed learning during their learning process.…”
Section: Discussioncontrasting
confidence: 59%
“…The present study revealed that the majority of undergraduate nursing students (90.52%) have high level of SDLR(score ≥150).This agree with ,Safavi et al(2010) who stated that majority of Jordanian and Iranian nursing students had high level of SDLR and perceived themselves as independent learner (14).In addition, the majority of students through SDL was a teaching method used alongside other methods, rather than a representation of beliefs about the adult self-learning (15). However, these results contradicted with the study of Lestari and Widjaja kusumah (2009) in Indonesia who indicates that 50% of the students had low to moderates scores for SDLR (16,17,18).These scores are slightly higher than those reported from previous studies in other countries. The mean reason may be: this study indicated that understanding the different components of SDL which are carried out by undergraduate nursing students are very important as study finding students can be adjust their SDL to direct the needs of the students, due to the undergraduate nursing students' state to look at Self-control in self-directed learning during their learning process.…”
Section: Discussioncontrasting
confidence: 59%
“…Each group then presents their findings to the class at the end of the three weeks period. The term project component of ENVS 4413 course itself consisted of five activity-based reflective journals, an industrial visit, group discussions, final report writing, and a group presentation [3].…”
Section: Term Projectmentioning
confidence: 99%
“…Moreover, term projects have explicit goals and it is teacher facilitated but not directed. They are designed to make a connection between activities and the underlying conceptual knowledge that one intend to foster [2][3][4][5]. Employment of term project instrument in environmental education became necessary in view of some changes in post secondary education policy in Alberta some years ago.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation